Size effects of fiscal policy and business confidence in the Euro area - Nektarios A. Michail; Christos S. Savva; Demetris Koursaros (International Journal of Financial Studies, 2017)
In the aftermath of the European sovereign debt crisis (2009-2014), the management of expectations has risen in importance. However, policy responses have emphasized the management of fiscal spending without examining the impact changes in the business confidence have on the economy. This paper uses a Factor-Augmented Vector Autoregressive specification, which allows for a larger information set covering both domestic and international developments, to measure the responses of five Euro Area economies to a one percent shock in government consumption and business confidence. The evidence suggests that even though the response to a government consumption shock is strong, a shock in expectations has an even greater effect. This points out to the fact that perceptions about the future and trust in the policymaker are much more important than previously considered. Thus, especially in (but not limited to) times of turbulence, or during efforts of stabilization and/or structural reforms, more emphasis should be placed on the overall credibility of the decisions, which could help to mitigate any potential adverse effects from the policies.
Keywords: E30; E61; E62; H30; 330; fiscal shocks; FAVAR; expectations; policy